2004
DOI: 10.1023/b:trag.0000026070.15253.88
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Demonstration of Transgenic Resistance to the Nematode Radopholus similis Conferred on Banana by a Cystatin

Abstract: Cavendish banana was transformed using Agrobacterium tumefaciens to express a protein engineered rice cystatin (OcIdeltaD86) of value for control of plant parasitic nematodes. Expression for each line was under control of a constitutive promoter from the maize ubiquitin gene (UBI-1), a constitutive, chimeric promoter from the octopine and mannopine synthase genes of A. tumefaciens or a promoter from a root-preferentially expressed tubulin gene Arabidopsis (TUB-1). Lines were selected as of potential interest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 9 publications
3
54
0
1
Order By: Relevance
“…The defense function has been inferred from the ability of PhyCys to inhibit the activity of digestive proteases from arthropods in vitro, in artificial diets as well as through bioassays on transgenic plants overexpressing PhyCys genes (Pernas et al, 1998;Atkinson et al, 2004;Ribeiro et al, 2006;Alvarez-Alfageme et al, 2007). Anti-mite activities and deleterious effects against phytopathogenic fungi and viruses have also been described for these inhibitors (Gutierrez-Campos et al, 1999;Pernas et al, 2000;Martinez et al, 2003;Abraham et al, 2006;Wang et al, 2008).…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%
“…The defense function has been inferred from the ability of PhyCys to inhibit the activity of digestive proteases from arthropods in vitro, in artificial diets as well as through bioassays on transgenic plants overexpressing PhyCys genes (Pernas et al, 1998;Atkinson et al, 2004;Ribeiro et al, 2006;Alvarez-Alfageme et al, 2007). Anti-mite activities and deleterious effects against phytopathogenic fungi and viruses have also been described for these inhibitors (Gutierrez-Campos et al, 1999;Pernas et al, 2000;Martinez et al, 2003;Abraham et al, 2006;Wang et al, 2008).…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%
“…Gene expression of cysteine proteinase inhibitors is closely related to the regulation of cysteine proteinase inhibitor proteins (Zhao et al, 1996). Cysteine proteinase inhibitors have been shown to affect nematode resistance, and have been used to protect various plant species including alfalfa, banana, rice, and tomato against a wide range of nematodes with diverse feeding strategies (Atkinson et al, 1996(Atkinson et al, , 2004Samac and Smigocki, 2003;Urwin et al, 1995Urwin et al, , 1997. These reports assumed repression of nematode parasitism was caused by an increase in cysteine proteinase inhibitor proteins, but our results indicated that RKN root invasion declines when cysteine proteinase inhibitor proteins increase in the plant root.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recombinant proteins with pesticidal, antidigestive or antifeedant properties have been identified or devised over the years for the development of herbivorous pest-resistant crops by genetic transformation (Carlini and Grossi-de-SĂĄ, 2002;Christou et al, 2006;Gatehouse, 2008;Zhu-Salzman et al, 2008). An engineered version of the rice cysteine protease inhibitor oryzacystatin I (OC-I) (Urwin et al, 1995) was shown, notably, to confer nematode resistance in transgenic banana lines genetically transformed with the corresponding transgene sequence (Atkinson et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%